Mycobacterium tuberculosis Central Metabolism Is Key Regulator of Macrophage Pyroptosis and Host Immunity - Michelle E. Maxson; Lahari Das; Michael F. Goldberg; Steven A. Porcelli; John Chan; William R. Jacobs (Pathogens, 2023)
Metabolic dysregulation in Mycobacterium tuberculosis results in increased macrophage apoptosis or pyroptosis. However, mechanistic links between Mycobacterium virulence and bacterial metabolic plasticity remain ill defined. In this study, we screened random transposon insertions of M. bovis BCG to identify mutants that induce pyroptotic death of the infected macrophage. Analysis of the transposon insertion sites identified a panel of fdr (functioning death repressor) genes, which were shown in some cases to encode functions central to Mycobacterium metabolism. In-depth studies of one fdr gene, fdr8 (BCG3787/Rv3727), demonstrated its important role in the maintenance of M. tuberculosis and M. bovis BCG redox balance in reductive stress conditions in the host. Our studies expand the subset of known Mycobacterium genes linking bacterial metabolic plasticity to virulence and also reveal that the broad induction of pyroptosis by an intracellular bacterial pathogen is linked to enhanced cellular immunity in vivo.